Conceptualizing Culture and Creativity: Perspectives on Creativity by Japanese Secondary School Students. (27th February 2022) - Karnilowicz Mizuno, Cassie; Xu, Lihua
Abstract: Creativity is generally considered a personal attribute, which is individualist and cognitive and less as a relational construct situated culturally and collectively. Past comparative cultural studies of creativity involving East Asian contexts focus on an individualist and cognitive perspective with relatively limited research investigating the cultural and collective aspects of creativity. This is a phenomenographic investigation of how creativity in the Visual Arts is conceptualized by Japanese adolescents. Participants included 14 students of Art and Shodo (Traditional Japanese Calligraphy) attending a co‐educational school in Tokyo. Students were interviewed individually or within a focus group to explore their understanding of creativity. Creativity in this context was associated primarily with "thinking" as a process rather than product‐orientated notions of creativity typical in the Western context. Our findings challenge understandings of creativity as a set of characteristics predominantly associated with tangible and quantitatively measurable cognitions regardless of context and suggest that understanding the richness of creativity should engage the socio‐cultural environment. In particular, Japanese cultural norms and language significantly influence how creativity is constituted and discerned. Students' complex, varied, and personal conceptualizations of creativity were mediated through their experiences with traditional or non‐traditional art.